Влияние клатратных комплексов β-циклодекстрина с регуляторами роста на морфологические и биохимические показатели барвинка малого Vinca minor L. - Лёшина, Л.Г.; Булко, О.В.; Рогальский, С.П.; Тарасюк, О.П.; Егорова, О.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. Study of the influence of clathrate complex of β-cyclodextrin with traditional growth regulators on morphological and biochemical parameters of periwinkle in the culture in vitro Methods. Insertion of growth regulators into β-cyclodextrin. In vitro cultivation. HPLC-analysis of secondary metabolites. Results. Periwinkle was cultivated in MC medium with addition of the complexes of plant growth regulators (2.4-D; BA; GA) with β-cyclodextrin. For comparison the plants were grown in the medium without в-cyclodextrin. It has been established that the insertion of β-cyclodextrin complexes with growth regulators stimulated plant growth by increasing the mass, lengthening of the steem and roots, increase of branching and rooting, as well as caused intensification of the biosynthesis of vincamine indole alkaloid. Moreover, the obtained complexes showed prolonged action on the culture of periwinkle callus cells. Conclusions. The complexes of growth regulators with β-cyclodextrin considerably change the properties of hormones, causing both morphological and biochemical changes of plants.